TINGKAT KECEMASAN SARJANA FRESH GRADUATE MENGHADAPI PERSAINGAN KERJA DAN MENINGKATNYA PENGANGGURAN INTELEKTUAL (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2012)
Abstrak. Penelitian ini bertujuan untuk untuk mengetahui gambaran secara deskriptif tingkat kecemasan sarjana fresh graduate menghadapi persaingan kerja dan meningkatnya pengangguran intelektual. Metode penelitian yang digunakan adalah metode kuantitatif deskriptif. Penelitian ini dilaksanakan di Universitas Negeri Semarang. Subjek penelitian berjumlah 205 alumni mahasiswa UNNES tahun 201 l yang ditentukan menggunakan teknik insidental sampling. Penelitian ini diukur menggunakan skala kecemasan. Uji analisis menggunakan teknik product moment dengan bantuan program SPSS 17.00 for windows.Hasil penelitian menunjukkan tingkat kecemasan tergolong dalam kategori rendah dengan perolehan hasil sebesar 52,7% atau 108 subjek. Hasil tersebut ditinjau dari antara lain aspek fisik dengan perolehan hasil terbanyak 64,4% atau 132 subjek pada kategori rendah, aspek behavior dengan perolehan hasil terbanyak 76,6% atau 157 subjek pada kategori sedang dan aspek kognitif dengan perolehan hasil terbanyak 64,4% atau 132 subjek pada kategori sedang.Kesimpulan yang didapat bahwa dapat dilihat secara umum pada Sarjana fresh graduate Unnes dalam menghadapi persaingan kerja dan pengangguran intelektual tergolong dalam kategori rendah. Hal ini menunjukkan bahwa responden lebih tenang dalam mengahadapl persamgan kerja yang semakin ketat dan adanya fenomena pengangguran intelektual sekarang. Kata kunci : kecemasan, fresh graduate Abstract. This research is the portrayal of the phenomenon condition about how difficult and hard the job competition after the students finish their study that it indirectly makes the anxiety to fresh graduate student. The fresh graduate student anxiety facing the competitive job and the intellectual unemployment is the psychological condition including the depression and the fearfulness which comes to anybody because there is a condition causing an individual threatened by something that make their fear and painful coming from the inside and outside of themselves so that those make the anxiety disturbing their health and restfulness which it is sometimes causing physical disturbance,This research aims to find out descriptively the portrayal of the fresh graduate student anxiety facing the job competition and the increasing of intellectual unemployment. The method of the research is descriptive quantitative method.Then, This research is taken in Semarang State University. Moreover, The number of the research subject is 205 fresh graduate students of UNNES on 201 l which is determined by using incidental sampling technique. Furthermore, This research is measured by using anxiety scale. The last, Analysis test uses product moment technique by applying SPSS l7_()0_/or windows program. The result of the research shows that the anxiety level is in low category with the result 52,7 % or 108 subject, The result is observed by physical aspect with the dominant result 64,4 % or 132 subject in low category, behavior aspect 76,6% or 157 subject in medium category, and cognitive aspect 64,4% or l32 subject in medium category with the dominant result.The conclusion can be concluded that mostly the fresh graduate student of UNNES in facing competitive job and intellectual unemployment is in low level category. The result shows that respondent is more repose-full facing the hardest job competition and the phenomenon of intellectual unemployment nowadays.